Generation mechanism of NOx and N2O precursors (NH3 and HCN) from aspartic acid pyrolysis: A DFT study - Peng, Kang; Wu, Qin; Tipeng, Wang; Zongqiang, Fu; Liwei, Ju; Zhongfu, Tan (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: In order to better understand the mechanism of NOx and N2O precursors (NH3 and HCN) from aspartic acid (Asp) pyrolysis, decomposition reaction networks resulting in the generation of NH3 and HCN were investigated by employing density function theory methods. After several pathways were analyzed in detail, two series of pyrolytic reactions containing three possible pathways were proposed. All the reactants, transition states, intermediates and products were optimized, also the electronic properties on these crucial points were discussed, which shows that Cα acts as the most active site to initiate the pyrolysis reaction, where the direct Cα-Cβ bond breakage, due to the atomic charge population of repulsion, led to one key route for the generation of HCN, and the transfer of Hα from Cα to Cβ resulting in another key route for the generation of HCN, while the transfer of Hα from Cα to N atom of Asp resulting in the key route for the generation of HN3. Further, the kinetic analysis based on speed control method in each key reaction pathway was conducted to further compare the generation of HCN and NH3 under various temperatures. The above results are in accordance with the related experimental results.Keywords: pyrolysis, aspartic acid (Asp), amino acid, DFTDOI: 10.3965/j.ijabe.20160905.2559Citation: Kang P, Qin W, Fu Z Q, Wang T P, Ju L W, Tan Z F. Generation mechanism of NOx and N2O precursors (NH3 and HCN) from aspartic acid pyrolysis: A DFT study. Int J Agric & Biol Eng, 2016; 9(5): 166－176.